Base-promoted radical decarboxylative coupling of N, N-Difluorobenzenesulfonamide and cinnamic acid. (9th January 2023) - Fei, Fan; Yang, Xianjin
Abstract: A base-promoted decarboxylative sulfonylation of cinnamic acids with N, N-difluorobenzenesulfonamide (DFBSAs) is developed. This study offers a highly efficient metal and oxidant-free strategy for the preparation of ( E )-vinyl sulfones. Moreover, the transformation is proposed to proceed via a radical process and exhibits broad substrate scopes and good functional group tolerance. Graphical abstract: To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Image 1